The Ancient miḥrāb of the Friday Mosque in Ronda (Malaga, Spain): Historical Evolution and Future Perspective - María Marcos Cobaleda; Sergio Ramírez González (Arts, 2025)
The aim of this article is to analyse the material remains of the ancient miḥrāb of the Friday Mosque in Ronda (Malaga, Spain), preserved in the present-day church of Santa María de la Encarnación la Mayor, and to propose preservation and valorisation measures to bring these remains to light. After the Christian conquest of Ronda, the church of Santa María de la Encarnación la Mayor was built on the site of the former Friday Mosque. In the 16th century, an altarpiece featuring niches and wall paintings was built, covering the plasterworks of the ancient miḥrāb. The primitive altarpiece was replaced by a Baroque one in the 17th century (El Sagrario altarpiece). At the beginning of the 20th century, the remains of the ancient miḥrāb and the 16th-century altarpiece were discovered while preparing the space for burial sites. Since then, a section of the plasterworks was recovered, although part of them remains covered by the 17th-century altarpiece. In this article, we analyse in detail the remains of the Islamic plasterworks that covered the qibla wall and the ancient miḥrāb, and propose a series of preservation and valorisation measures aimed at restoring these remains, without damaging the 17th-century altarpiece.